2021
DOI: 10.2981/wlb.00740
|View full text |Cite
|
Sign up to set email alerts
|

Don't go chasing the ghosts of the past: habitat selection and site fidelity during calving in an Arctic ungulate

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Using the latter approach, we found that calving‐sequences of caribou expressing spatial fidelity were on average ~ 1.0 km apart, which was considerably less than individuals that did not express spatial fidelity (~15.7 km). This mean distance is closer than previously reported in sedentary woodland caribou in Quebec and Labrador (6.7 km, Schaefer et al., 2000), in woodland caribou in the central mountains of British Columbia and Alberta, Canada (8.7 km, Nobert et al., 2016), and in Svalbard reindeer ( R. t. platyrhynchus , 1.5–3.9 km, Garfelt‐Paulsen et al., 2021). In fact, three caribou observed in this study calved within 50 m of the site where they calved the previous year.…”
Section: Discussionsupporting
confidence: 41%
“…Using the latter approach, we found that calving‐sequences of caribou expressing spatial fidelity were on average ~ 1.0 km apart, which was considerably less than individuals that did not express spatial fidelity (~15.7 km). This mean distance is closer than previously reported in sedentary woodland caribou in Quebec and Labrador (6.7 km, Schaefer et al., 2000), in woodland caribou in the central mountains of British Columbia and Alberta, Canada (8.7 km, Nobert et al., 2016), and in Svalbard reindeer ( R. t. platyrhynchus , 1.5–3.9 km, Garfelt‐Paulsen et al., 2021). In fact, three caribou observed in this study calved within 50 m of the site where they calved the previous year.…”
Section: Discussionsupporting
confidence: 41%
“…Moreover, herbivores, and reindeer particularly, can influence vegetation via grazing, trampling and manuring which can lead to the vegetation becoming dominated by a thick layer of mosses with interspersed graminoids and forbs 29 31 . While the sea bird colonies are concentrated on coastal cliffs, reindeer have occupied the whole land area of Svalbard 32 , also shallow mountain slopes where topographical conditions favour peat formation 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, increase in both male and female home ranges in spring may be related to the seasonal altitudinal migration to mountain meadows ( Viana et al 2018 ). Furthermore, reduction in female home range size after giving birth is likely due to the restricted mobility of their newborn kids ( Garfelt-Paulsen et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%